Emergence of 2009A/H1N1 cases in a tertiary care hospital in New Delhi, India - Broor, Shobha (Influenza Other Respir Viruses, 2011)
Please cite this paper as: Broor et al. (2011) Emergence of 2009A/H1N1 cases in a tertiary care hospital in New Delhi, India. Influenza and Other Respiratory Viruses 5(6), e552–e557. Objective  To determine virologic and epidemiologic characteristics of pandemic (H1N1) 2009 at All India Institute of Medical Sciences (AIIMS) a tertiary care hospital in New Delhi, India. Methods  Nasal and throat swabs from patients with febrile acute respiratory illness (FARI) from August to December 2009 (n = 1401) were tested for 2009A/H1N1 and seasonal influenza A viruses by real‐time RT‐PCR. Results  Of 1401 samples tested, 475 (33·9%) were positive for influenza A, of these majority (412; 87%) were 2009A/H1N1, whereas the remaining 63 (13%) were seasonal influenza A (49 were A/H3 and 14 were A/H1). While co‐circulation of 2009A/H1N1 and A/H3 was observed in August–September, subsequent months had exclusive pandemic influenza activity (October–December 2009). Pandemic 2009A/H1N1 emergence did not follow typical seasonal influenza seasonality in New Delhi, which normally peaks in July–August, but instead showed bimodal peaks in weeks 39 and 48 in 2009. The percent of specimens testing positive for 2009A/H1N1 influenza virus was found to be highest in >5‐ to 18‐year age group (41·2%; OR = 2·3; CI = 1·6–3·2; P = 0·00). Conclusions  Taken together, our data provide high prevalence of pandemic 2009A/H1N1 in urban New Delhi with bimodal peaks in weeks 39 and 48 and highest risk group being the children of school‐going age (aged >5–18).